2020
DOI: 10.1186/s12885-020-07147-y
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram model to predict death rate among non-small cell lung cancer (NSCLC) patients with surgery in surveillance, epidemiology, and end results (SEER) database

Abstract: Background: This study aimed to establish a novel nomogram prognostic model to predict death probability for non-small cell lung cancer (NSCLC) patients who received surgery.. Methods: We collected data from the Surveillance, Epidemiology, and End Results (SEER) database of the National Cancer Institute in the United States. A nomogram prognostic model was constructed to predict mortality of NSCL C patients who received surgery. Results: A total of 44,880 NSCLC patients who received surgery from 2004 to 2014 w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…The significantly higher C-index of the nomogram (in both cohorts) compared with the AJCC staging model indicates the good discrimination ability of the nomogram. This indicated that the model is very precise ( 42 ). In the current study, calibration plots of predictions corresponded well with actual observations indicated by the curve being close to the 45-degree line, verifying the repeatability and reliability of the established nomogram ( 20 , 42 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The significantly higher C-index of the nomogram (in both cohorts) compared with the AJCC staging model indicates the good discrimination ability of the nomogram. This indicated that the model is very precise ( 42 ). In the current study, calibration plots of predictions corresponded well with actual observations indicated by the curve being close to the 45-degree line, verifying the repeatability and reliability of the established nomogram ( 20 , 42 ).…”
Section: Discussionmentioning
confidence: 95%
“…This indicated that the model is very precise ( 42 ). In the current study, calibration plots of predictions corresponded well with actual observations indicated by the curve being close to the 45-degree line, verifying the repeatability and reliability of the established nomogram ( 20 , 42 ). This is the first nomogram constructed to predict the survival of elderly AC patients that we know of.…”
Section: Discussionmentioning
confidence: 95%
“…20 Our profiling maintains essential insights into PACC and offers valuable knowledge on the morbidity, predictive factors, and survival of patients with PACC, following the analogous statistical methods. 21 In conclusion, our population-based study has demonstrated that PACC is a rare lung adenocarcinoma with an increasing incidence trend, particularly in men. Surgery is related to a better prognosis and should be considered for patients with PACC.…”
Section: Discussionmentioning
confidence: 60%
“… 20 Our profiling maintains essential insights into PACC and offers valuable knowledge on the morbidity, predictive factors, and survival of patients with PACC, following the analogous statistical methods. 21 …”
Section: Discussionmentioning
confidence: 99%
“…The nomogram is a useful and popular visual graph that illustrates the probability of occurrence of predicted events so as to guide clinical treatments [12][13][14]. Several past studies have reported that nomogram has good risk-prediction ability for post-surgical survival prognostication in patients with malignant tumors [15,16]. However, reports on the use of a nomogram model for predicting the risk of thrombosis are limited [17].…”
Section: Introductionmentioning
confidence: 99%